Rapid and High-Throughput Detection of Peripheral Blood Chromosome Aberrations in Radiation Workers. Issue 2 (16th April 2019) - Bi, Jinling; Dai, Hong; Feng, Junchao; Bian, Huahui; Chen, Weibo; Wang, Youyou; Liu, Yulong; Huang, Yong
There is a pressing need to establish automated solutions for the rapid, high-throughput, and automatic detection of chromosome aberrations (CAs) in the occupational health surveillance of large-scale radiation workers. Here, we described and verified the accuracy of a new measurement system based on the automatic scanning and analysis of dicentric chromosomes (DICs). The effects of cell number on DIC detection by automatic scanning and analysis were studied, and the distribution of DIC values per cell was calculated. In total, 1088 cases were detected by automatic DIC scanning and analysis in 26 663 radiation workers, and 73 cases were further confirmed by a technician, including 5 cases in which radiation exposure lead to harmful medical consequences. Our approach reduces the workload by 96% and increases the speed of assessment approximately 7-fold. Overall, this study validates the utility of a novel rapid and high-throughput CA detection procedure as a means of occupational health surveillance of large-scale radiation workers.